Analisis Faktor-Faktor yang mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi Pengguna E-Commerce - Patriandari Patriandari; Anis Safitri (AKRUAL : Jurnal Akuntansi dan Keuangan, 2021)
The purpose of this study is to analyze the effect of E-commerce User Taxpayer Compliance on Online Shopping Entrepreneurs operating at OLX.co.id. The number of samples is 50 Online Shopping entrepreneurs, all of whom are respondents included in this study. This research was conducted using primary data with questionnaires. The data analysis technique used in this study is Multiple Linear Regression, which is operated through the SPSS program version 22.. Hypothesis testing with t test shows that the variable of taxpayer awareness does not have a significant effect on taxpayer compliance. While Understanding of Taxation Regulations, and the Level of Trust of Taxpayers in the Government System has a significant effect on Taxpayer Compliance.